MASS MEDIA AND CORRUPTION: UKRAINIAN REALITIES - Гринь, І. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
Such phenomenon as a corruption in mass-media, its origin, formation and media relations with other spheres of political life of the country is considered. Their role in political life is analyzed.        Such functions of them, as mobilization and informative ones, function of socialization, function of expression of interests of society and function of public opinion formation are distinguished. Duties, possibilities of mass media, and also problems that appear in front of them, are explained. The major functions of mass media and order of their use are distinguished for the different political regimes, in particular at authoritarian, totalitarian and democratic ones. The features of their functioning in terms of the democratic regimes are analyzed.The main mass media weaknesses, such as its corruption, ordered media plots that reflect business or political divergences and lack of own journalistic investigations are determined. The role of printed and electronic mass media is distinguished. The priority attention to the television, broadcast and the Internet communication is given.  The main attention is given to the determination of Ukrainian mass media development level in the estimation of international organizations, in particular Reporters without borders, and informative centers, for example, «Detector of Medias», and also the illumination of different countries’ events in their reports. The main suppliers of media information, their owners are distinguished.The concept of media corruption, its role in modern media space of Ukraine is considered. The features of state, municipal and commercial mass media are distinguished. The influence on forming of the «agenda», that provides efficient communication of publicity and executives is analyzed.